The impact of caries experience on quality of life among dental students in Iraq - Jenan K Almaas; Ban S Diab (College of Dentistry/ University of Baghdad, 2020)
Background: Dental caries is generally given the highest priority in national oral health services for adult populations. Yet, there is no study which has explored the impact on quality of life specifically related to dental caries in samples of dental students. The purpose of the current study was to assess the impact of caries experience on quality of life among dental students in three governorates in Iraq. Materials and Methods: This observational study included 1364 dental students aged 18-22 years old, from three governorates. Information on quality of life was obtained from a structured, self-administered questionnaire from the students who were willing to participate in the study. The data was collected, summarized and statistically analyzed. Caries experience in the present study was determined by the Decayed- Missing Filled Surfaces (DMFS) indexed by WHO in 1997 in which all teeth were examined and all the third molars were included. Results: Regarding dental caries and the four Quality of Life domains, in each domain scores, DS component had the highest contribution to the DMFS followed by the MS component while FS components had the lowest contribution to the index. On the other hand, DMFS showed the lowest mean among the good scores of all domains and it had the highest mean among the poor type. Conclusion: The quality of life among dental students is associated with caries severity as the DMFS and its components affected different domains regarding quality of life. Keywords: caries experience, dental students, quality of life.